Battery fire extinguishing agent and preparation method and application thereof

By using water, hydrated salts and auxiliary materials (such as nanoparticles or organic binders) in lithium battery fire extinguishing agents, a material that can inhibit film boiling under high temperature conditions is formed, which solves the shortcomings of existing fire extinguishing agents in extinguishing lithium battery fires, and achieves the effect of rapid cooling and effective prevention of fire propagation.

CN119607491APending Publication Date: 2025-03-14深圳普瑞赛思检测科技股份有限公司 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411590000.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing fire extinguishing agents are difficult to effectively extinguish lithium battery fires, especially in preventing the heat spread of the battery from being heat out of control, and the fire extinguishing effect is poor.

Method used

A battery fire extinguishing agent is used, and the preparation raw materials include water, hydrated salts and auxiliary materials, which include nanoparticles or organic binders. The mass fraction of the hydrated salts is 10% to 80%. Through the combination of these components, a material that can effectively inhibit film boiling under high temperature conditions is formed.

Benefits of technology

The battery fire extinguishing agent can significantly increase the critical temperature of film boiling, increase it by more than 250℃, significantly improve the fire extinguishing cooling effect of the fire extinguishing agent, quickly cool down and effectively prevent the spread of lithium battery fires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607491A_ABST
    Figure CN119607491A_ABST
Patent Text Reader

Abstract

The invention discloses a battery fire extinguishing agent and a preparation method and application thereof. Preparation raw materials of the battery fire extinguishing agent comprise water, hydrated salts and auxiliary materials, the auxiliary materials comprise at least one of nano-particles or an organic binder, and the mass fraction of the hydrated salts in the preparation raw materials is 10%-80%. The battery fire extinguishing agent contains high-concentration hydrated salts, can effectively inhibit the occurrence of membrane boiling, and can interact with the nanoparticles and the organic binder to remarkably improve the fire extinguishing capacity and the cooling effect of the fire extinguishing agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fire extinguishing agents, and in particular relates to a battery fire extinguishing agent and a preparation method and application thereof. Background Art

[0002] Lithium batteries are increasingly used, and the market demand for lithium batteries is expanding year by year. The application of lithium batteries has extended from digital products to transportation power, energy storage, aerospace, communication backup power, etc. Although the large-scale use of electric vehicles using lithium battery technology has facilitated people's lives, the fire safety issues that come with it cannot be ignored.

[0003] Compared with ordinary fires, lithium battery fires have the characteristics of high combustion temperature, strong heat radiation, easy to cause casualties, and difficult to extinguish. Lithium battery fires are often caused by thermal runaway of lithium batteries. The process can be roughly divided into: ① Due to high temperature, damage and other conditions of the battery, the battery thermal runaway is triggered, and the battery temperature rises to above 800℃ in a very short time; ② The high temperature generated by the first thermal runaway battery ignites the combustibles inside and outside the battery, causing fire and explosion; ③ The high temperature and flames generated by the first thermal runaway battery cause the surrounding batteries to continue to heat up and run away, returning to step ① to cycle, and thermal runaway propagates. In lithium battery fires, "fire extinguishing" is not the key, because simply extinguishing the fire cannot prevent the heat from the thermal runaway of the first battery to spread and cause new battery thermal runaway. The key to lithium battery fires is to quickly reduce the temperature of the battery that has already experienced thermal runaway to below the safe temperature.

[0004] However, at present, conventional fire extinguishing agents such as dry powder, aerosol fire extinguishing agents, heptafluoropropane, perfluorohexanone, etc. only have the ability to extinguish open flames, and have no cooling ability or poor cooling ability. It is difficult to fundamentally extinguish fires caused by lithium batteries, and the fire extinguishing effect is poor. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a battery fire extinguishing agent, which has the characteristics of fast cooling, good cooling effect and good fire extinguishing effect.

[0006] The invention also provides a method for preparing the battery fire extinguishing agent.

[0007] The present invention also provides application of the battery fire extinguishing agent.

[0008] In a first aspect of the present invention, a battery fire extinguishing agent is provided, wherein the raw materials for preparing the battery fire extinguishing agent include water, hydrated salts and auxiliary materials, wherein the auxiliary materials include at least one of nanoparticles or organic binders, and the mass fraction of the hydrated salts in the raw materials for preparing the battery fire extinguishing agent is 10% to 80%.

[0009] The battery fire extinguishing agent according to the embodiment of the present invention has at least the following beneficial effects:

[0010] The battery fire extinguishing agent in the present invention contains a high concentration of hydrated salts. When it is sprayed on the surface of a high-temperature battery (such as the high-temperature metal surface of a thermal runaway battery), salt crystals will precipitate and adhere to the metal surface, which can inhibit the film boiling of water and perform nucleate boiling with a higher heat transfer coefficient. The salt solution material that undergoes nucleate boiling can further precipitate and deposit more salt crystals on the metal surface. Among them, the salt crystals mainly play the following roles: ① Inorganic salts are soluble in water, so it can be regarded as that the surface contact angle of water on the inorganic salt is extremely small, and the interaction force between the solid and the liquid is large, which can make the subsequent sprayed materials spread more smoothly on the surface, prevent the formation of a steam film, and have a larger heat exchange area; ② The roughness of the inorganic salt crystals is relatively high (the precipitated inorganic salt crystals are rougher than the metal surface, and the higher the roughness, the more difficult it is to form a steam film), and it is difficult for the liquid to form a gas film on its surface to cause film boiling.

[0011] Nanoparticles provide crystallization sites for the precipitation of inorganic salts, accelerate the precipitation of decomposition products, and improve the ability to inhibit film boiling. Organic binders can increase the viscosity of fire extinguishing agents, so that the time the fire extinguishing agent material stays in the thermal runaway high-temperature battery increases; increase the adhesion of solid particles on the battery surface, inhibit water film boiling; and organic binders can form loose and porous carbon materials under high temperature and combustion conditions, which also have the effect of inhibiting water film boiling.

[0012] The high-concentration salts in the battery fire extinguishing agent of the present invention can interact with nanoparticles and organic binders. The organic binder increases the residence time of water on the high-temperature surface, and the binder itself forms a porous carbon material at high temperature to change the surface roughness. The nanoparticles provide crystallization sites for the deposition of inorganic salts. The hydrated salts absorb a large amount of heat and decompose inorganic salts to increase the surface hydrophilicity, and finally synergistically form a surface with porous, rough and hydrophilic properties, thereby effectively increasing the temperature at which film boiling occurs (critical membrane boiling temperature, LFP) by more than 250°C compared with pure water, significantly improving the fire extinguishing ability and cooling effect of the battery fire extinguishing agent.

[0013] The battery fire extinguishing agent of the present invention has good stability and can be placed in a room temperature environment for a long time without stratification or crystal precipitation, which is conducive to the long-term storage of the battery fire extinguishing agent product.

[0014] In some embodiments of the present invention, the hydrated salts include salts that can undergo thermal decomposition. Optionally, the thermal decomposition temperature of the hydrated salts is below 150°C.

[0015] In some embodiments of the present invention, the salt capable of thermal decomposition includes at least one of disodium hydrogen phosphate dodecahydrate (DHPD), sodium dihydrogen phosphate dihydrate, magnesium sulfate heptahydrate, sodium sulfate decahydrate, ammonium phosphate trihydrate, sodium bicarbonate heptahydrate, sodium bicarbonate decahydrate, calcium carbonate hexahydrate, sodium carbonate decahydrate, ammonium ferric sulfate dodecahydrate, aluminum sulfate 18hydrate, sodium aluminum silicate nonahydrate, or sodium thiosulfate pentahydrate.

[0016] In some embodiments of the present invention, the hydrated salts include at least one of disodium hydrogen phosphate dodecahydrate, magnesium sulfate heptahydrate, sodium sulfate decahydrate, aluminum sulfate 18hydrate, potassium aluminum sulfate dodecahydrate, sodium thiosulfate pentahydrate, copper sulfate heptahydrate, sodium dihydrogen phosphate dihydrate, ammonium phosphate trihydrate, sodium bicarbonate heptahydrate, sodium bicarbonate decahydrate, calcium carbonate hexahydrate, sodium carbonate decahydrate, ammonium ferric sulfate dodecahydrate, aluminum sulfate 18hydrate, sodium aluminum silicate nonahydrate, sodium acetate trihydrate, calcium chloride hexahydrate, sodium silicate pentahydrate, lithium chloride trihydrate, cobalt chloride hexahydrate, aluminum nitrate nonahydrate, calcium sulfate dihydrate or ferrous sulfate heptahydrate.

[0017] In some embodiments of the present invention, the mass fraction of the hydrated salt in the preparation raw material is 15% to 45%.

[0018] Through the above implementation, the higher the concentration of the salt solution, the higher the critical temperature of the solution itself for film boiling. For example, the critical temperature of pure water for film boiling is about 300°C, and in some embodiments of the invention, when the salt concentration in the fire extinguishing agent is 20wt%, the critical temperature of film boiling can reach about 550°C, which is increased by about 250°C, thereby significantly improving the fire extinguishing cooling effect of the fire extinguishing agent.

[0019] In some embodiments of the present invention, the nanoparticles include at least one of nano-aluminum oxide, nano-copper oxide, nano-titanium oxide or nano-graphite powder.

[0020] In some embodiments of the present invention, the average particle size of the nanoparticles is 30 to 100 nm.

[0021] In some embodiments of the present invention, the mass fraction of the nanoparticles in the preparation raw material is 0.2% to 5%, such as 0.2% to 2%.

[0022] In some embodiments of the present invention, the organic binder includes at least one of polyvinyl alcohol, sodium polyacrylate or carboxymethyl cellulose.

[0023] Through the above implementation, the organic binder can increase the viscosity of the fire extinguishing agent, thereby increasing the time that the fire extinguishing agent material stays on the battery to be extinguished; increasing the adhesion of solid particles (such as salt decomposition products) on the battery surface, and the stable retention of the decomposition products on the surface of the lithium battery is the key to inhibiting water film boiling; the binder can form a loose and porous carbon material under high temperature and combustion conditions, which also has the effect of inhibiting water film boiling.

[0024] In some embodiments of the present invention, the mass fraction of the organic binder in the preparation raw material is 0.1% to 2%, such as 0.1% to 1%.

[0025] In some embodiments of the present invention, the auxiliary material further includes a surfactant.

[0026] In some embodiments of the present invention, the surfactant includes at least one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, Triton 100, Tween 60, Span 60 or polyether-modified silicone oil.

[0027] Through the above implementation, the surfactant can reduce the surface tension and contact angle of the fire extinguishing agent, so that the material can be better spread on the surface of the high-temperature object, increase the heat exchange area, and at the same time further increase the temperature at which film boiling occurs in the material, thereby inhibiting film boiling, enhancing cooling performance, improving cooling efficiency, and improving the battery fire extinguishing effect of the battery fire extinguishing agent.

[0028] In some embodiments of the present invention, the mass fraction of the surfactant in the preparation raw material is 0.2% to 5%, such as 0.2% to 1%.

[0029] In some embodiments of the present invention, the mass fraction of water in the raw material is 19% to 84%, and can be 20% to 84%. Water provides ultra-high vaporization enthalpy and absorbs a large amount of heat generated by the battery. The water here refers to raw water, excluding water contained in hydrated salt.

[0030] In some embodiments of the present invention, the mass fraction of water in the preparation raw material is 50% to 84%, and can further be 50% to 70%.

[0031] The second aspect of the present invention provides a method for preparing a battery fire extinguishing agent, comprising the following steps: mixing water, hydrated salts and auxiliary materials to obtain the battery fire extinguishing agent.

[0032] In some embodiments of the present invention, the temperature of the mixing step is 15-70°C, such as 40-70°C, specifically 60°C.

[0033] In some embodiments of the present invention, the hydrated salts include at least one of disodium hydrogen phosphate dodecahydrate, magnesium sulfate heptahydrate, sodium sulfate decahydrate, aluminum sulfate 18hydrate, potassium aluminum sulfate dodecahydrate, sodium thiosulfate pentahydrate, copper sulfate heptahydrate, sodium dihydrogen phosphate dihydrate, ammonium phosphate trihydrate, sodium bicarbonate heptahydrate, sodium bicarbonate decahydrate, calcium carbonate hexahydrate, sodium carbonate decahydrate, ammonium ferric sulfate dodecahydrate, aluminum sulfate 18hydrate, sodium aluminum silicate nonahydrate, sodium acetate trihydrate, calcium chloride hexahydrate, sodium silicate pentahydrate, lithium chloride trihydrate, cobalt chloride hexahydrate, aluminum nitrate nonahydrate, calcium sulfate dihydrate or ferrous sulfate heptahydrate.

[0034] The hydrated salt is a thermochemical energy storage material (TESM), which provides chemical decomposition enthalpy (may have a decomposition enthalpy greater than 1200 J / g), and the decomposition rate is faster than the vaporization of water, which can promote the boiling heat exchange rate of the material. The thermochemical energy storage material has a large density and does not change the volume enthalpy value of the fire extinguishing agent. The difference between the volume enthalpy value of the obtained fire extinguishing agent and pure water is small, and it has a strong cooling performance; the ions of the thermochemical heat storage material can react with flame free radicals (metal cations can react with flame free radicals to weaken the combustion reaction), which improves the fire extinguishing performance. The decomposition temperature of the hydrated salt is low (such as about 100°C), which can make the battery still absorb heat by chemical decomposition reaction before dropping to a safe temperature (such as about 120°C). And the deposition of decomposition products can change the surface properties, which can inhibit the film boiling of water under high temperature conditions, and film boiling will make the water residence time short and the cooling rate low, so TESM effectively improves the utilization rate of the cooling performance of the battery fire extinguishing agent.

[0035] At the same time, surfactants can reduce the surface tension and contact angle of materials, and can also inhibit the film boiling of water. Thermochemical heat storage materials can cooperate with surfactants to inhibit the film boiling of water and improve the heat exchange and cooling performance of water.

[0036] Therefore, the fire extinguishing agent in the present invention can inhibit the film boiling phenomenon under high temperature conditions, and the hydrated salt can increase the critical temperature of water film boiling. At the same time, the salt deposited by the hydrated salt can further inhibit the occurrence of film boiling. And the hydrated salt used is a thermochemical energy storage material, which has the characteristics of high thermal decomposition enthalpy, and can inhibit the film boiling of water without basically losing the vaporization enthalpy of the fire extinguishing agent (water-based material); the phosphate ions contained in the thermochemical energy storage material have a flame retardant effect. When a lithium battery has thermal runaway and burns, the maximum temperature can reach more than 800°C, and the fire extinguishing agent in the present invention has an efficient cooling effect under high temperature conditions, and has a good application prospect in the field of lithium battery fire extinguishing.

[0037] In some embodiments of the present invention, the preparation method comprises the following steps:

[0038] S1, mixing water and hydrated salt to obtain material A;

[0039] S2, mixing material A, a surfactant and an organic binder to obtain material B;

[0040] S3, mixing and dispersing the material B and the nanoparticles to obtain the battery fire extinguishing agent.

[0041] In some embodiments of the present invention, in step S1, water and hydrated salt are mixed at 40-70° C. to obtain material A.

[0042] In some embodiments of the present invention, in step S2, the mixing temperature of material A, surfactant and organic binder can be selected to be 15-50°C.

[0043] In some embodiments of the present invention, in step S3, the mixing temperature of material B and nanoparticles can be selected to be 15-50°C.

[0044] In some embodiments of the present invention, in step S3, the dispersion method includes ultrasonic dispersion, and optionally, the ultrasonic dispersion time is 1 to 6 hours.

[0045] The third aspect of the present invention provides the use of the battery fire extinguishing agent in a battery fire extinguishing product.

[0046] The battery fire extinguishing agent of the present invention can be used for fires caused by various types of batteries including but not limited to lithium batteries. In some embodiments of the present invention, the battery includes at least one of a lithium ion battery or a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0048] Figure 1 This is a schematic diagram of the principle of increasing the film boiling temperature by the hydrated salt in the battery fire extinguishing agent in Example 5 of the present invention;

[0049] Figure 2 The cooling curve diagram of the battery fire extinguishing agent cooling metal block of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6;

[0050] Figure 3 This is a comparison chart of the time required for the battery fire extinguishing agent to cool a metal block to the termination temperature in Examples 1 to 3 of the present invention and Comparative Examples 1 to 6;

[0051] Figure 4 This is a comparison chart of the average cooling rate of the battery fire extinguishing agent cooling metal block of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6;

[0052] Figure 5 This is a comparison chart of the average cooling rate of the battery fire extinguishing agent cooling metal block of Examples 1 to 3 of the present invention and Comparative Examples 2 to 6 compared with Comparative Example 1;

[0053] Figure 6 It is a comparison diagram of cooling curves of battery fire extinguishing agent cooling metal blocks of Example 1 of the present invention and Comparative Example 7;

[0054] Figure 7 This is a DSC test result diagram of the battery fire extinguishing agent A-D20 in Example 5 of the present invention;

[0055] Figure 8 This is a DSC test result diagram of the battery fire extinguishing agent of Comparative Example 8;

[0056] Fig. 9 This is a graph showing the test results of the physical properties of a series of battery fire extinguishing agents and DHPD in Example 5 of the present invention;

[0057] Fig.10 This is a graph showing the test results of the film boiling inhibition performance of a series of battery fire extinguishing agents and DHPD in Example 5 of the present invention;

[0058] Fig.11 This is a battery fire extinguishing test result diagram of a series of battery fire extinguishing agents and a conventional fire extinguishing agent in Example 5 of the present invention;

[0059] Fig.12 These are images of a battery thermal runaway test and a picture of the battery after being extinguished by the fire extinguishing agent of Example 5 of the present invention. DETAILED DESCRIPTION

[0060] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0061] The experimental methods without specific conditions in the following examples and comparative examples are generally based on conventional conditions in the art or conditions recommended by the manufacturers; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents available from commercial channels such as conventional markets.

[0062] The average particle size of nano-alumina is 30-100nm; the average particle size of nano-graphite powder is 30-100nm;

[0063] The average molecular weight of sodium polyacrylate is 150,000;

[0064] Example 1

[0065] This embodiment discloses a battery fire extinguishing agent, the preparation process of which includes the following steps:

[0066] Pure water and hydrated salt are mixed at 60°C until the hydrated salt melts, and stirred until homogeneous to obtain material A. Material A, surfactant, and organic binder are mixed at room temperature until the material is completely dissolved to obtain material B. Material B is mixed with nanoparticles, and ultrasonically dispersed at room temperature for 3 hours (power 500W) to obtain the battery fire extinguishing agent. The mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 58:0.5:40:1:0.5.

[0067] The hydrated salt is disodium hydrogen phosphate dodecahydrate; the nanoparticles are nanoalumina; the organic binder is sodium polyacrylate; and the surfactant is Triton 100.

[0068] The battery fire extinguishing agent in this embodiment can be used for fires caused by batteries such as lithium ion batteries or sodium ion batteries.

[0069] Example 2

[0070] This embodiment discloses a battery fire extinguishing agent, which is different from Embodiment 1 only in that in this embodiment: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 58.5:0.5:40:1:0.

[0071] Example 3

[0072] This embodiment discloses a battery fire extinguishing agent, which is different from Embodiment 1 only in that in this embodiment: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 59:0.5:40:0:0.5.

[0073] Example 4

[0074] This embodiment discloses a battery fire extinguishing agent, which is different from Embodiment 1 only in that in this embodiment: the mass ratio of pure water, hydrated salt, nanoparticles, organic binder and surfactant is 78:20:1:0.5:0.5.

[0075] Example 5

[0076] This embodiment discloses a series of battery fire extinguishing agents, which differ from the embodiment 1 only in that in this embodiment: the nanoparticles contained in this embodiment are nanographite powder, and the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder in the battery fire extinguishing agent is (96.5-x): 2: x: 1: 0.5. The battery fire extinguishing agents of a series of concentrations in this embodiment are recorded as A-Dx.

[0077] Comparative Example 1

[0078] This comparative example discloses a battery fire extinguishing agent, which is different from Example 1 only in that in this comparative example: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 100:0:0:0:0.

[0079] Comparative Example 2

[0080] This comparative example discloses a battery fire extinguishing agent, which is different from Example 1 only in that in this comparative example: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 99.5:0.5:0:0:0.

[0081] Comparative Example 3

[0082] This comparative example discloses a battery fire extinguishing agent, which is different from Example 1 only in that in this comparative example: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 59.5:0.5:40:0:0.

[0083] Comparative Example 4

[0084] This comparative example discloses a battery fire extinguishing agent, which is different from Example 1 only in that in this comparative example: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 98.5:0.5:0:1:0.

[0085] Comparative Example 5

[0086] This comparative example discloses a battery fire extinguishing agent, which is different from Example 1 only in that in this comparative example: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 99:0.5:0:0:0.5.

[0087] Comparative Example 6

[0088] This comparative example discloses a battery fire extinguishing agent, which is different from Example 1 only in that in this comparative example: the mass ratio of pure water, surfactant, hydrated salt, nanoparticles and organic binder is 98:0.5:0:1:0.5.

[0089] Comparative Example 7

[0090] This comparative example discloses a battery fire extinguishing agent, which differs from Example 1 only in that in this comparative example: an equal mass of NaCl is used to replace the hydrated salt in Example 1.

[0091] Comparative Example 8

[0092] This comparative example discloses a battery fire extinguishing agent, which differs from comparative example 7 only in that in this comparative example: the mass ratio of the pure water, surfactant, NaCl, nanoparticles and organic binder is 76.5:2:20:1:0.5, and the nanoparticles in this comparative example are nanographite powder.

[0093] Test example

[0094] This test example performs performance tests on the battery fire extinguishing agents prepared in the examples and comparative examples, specifically including:

[0095] (1) Metal cooling test simulating high-temperature battery surface: A metal block (316 stainless steel) was used for cooling effect test to simulate the cooling effect during battery fire. The cooling effect test of the metal block included: dripping each battery fire extinguishing agent at the same flow rate onto the surface of each preheated metal block (initial temperature 800°C), measuring the temperature change at the center of the metal block, and continuously dripping the battery fire extinguishing agent until the temperature of the metal block cooled to the same termination temperature (120°C). The main purpose was to examine the cooling time required.

[0096] Figure 2 is the cooling curve of each battery fire extinguishing agent cooling metal block; the corresponding cooling time of each curve is: ①369s; ②364s; ③168s; ④369s; ⑤365s; ⑥146s; ⑦145s; ⑧331s; ⑨105s;

[0097] Figure 3 It is a comparison chart of the time required for each battery fire extinguishing agent to cool the metal block to the termination temperature;

[0098] Figure 4 It is a comparison chart of the average cooling rate of the metal blocks cooled by the fire extinguishing agents of each battery;

[0099] Figure 5 is a comparison chart showing the percentage increase of the average cooling rate of the cooling metal blocks of each battery fire extinguishing agent compared to the average cooling rate of the battery fire extinguishing agent of Comparative Example 1;

[0100] in Figures 2 to 5 middle:

[0101] ①: represents the test results of the battery fire extinguishing agent of comparative example 1;

[0102] ②: represents the test results of the battery fire extinguishing agent of comparative example 2;

[0103] ③: represents the test results of the battery fire extinguishing agent of comparative example 3;

[0104] ④: represents the test results of the battery fire extinguishing agent of comparative example 4;

[0105] ⑤: represents the test results of the battery fire extinguishing agent of comparative example 5;

[0106] ⑥: represents the test results of the battery fire extinguishing agent of Example 2;

[0107] ⑦: represents the test results of the battery fire extinguishing agent of Example 3;

[0108] ⑧: represents the test results of the battery fire extinguishing agent of Comparative Example 6;

[0109] ⑨: represents the test results of the battery fire extinguishing agent of Example 1.

[0110] Depend on Figures 2 to 5 It can be seen that compared with Comparative Example 1, the battery fire extinguishing agent of Example 1 has a cooling effect on the metal block that is improved by 251%, which is higher than the improvement of other embodiments and comparative examples compared with Comparative Example 1. From the results, it can be seen that the cooling performance of the comparative example containing no hydrated salt and only auxiliary materials is at a level comparable to that of pure water itself; while Comparative Example 3 and Examples 2 to 3 containing hydrated salts can improve the cooling performance of pure water, and the average cooling rate is increased by up to 154% compared with Comparative Example 1; after adding nanoparticles and organic binders at the same time on the basis of adding hydrated salts, the average cooling rate of the material can be increased by 251% compared with Comparative Example 1, proving that the hydrated salts, nanoparticles, and organic binders synergistically improve the cooling effect of the fire extinguishing agent.

[0111] Figure 6 The cooling curve comparison diagram of the battery fire extinguishing agent cooling the metal block of Example 1 and Comparative Example 7 shows that the cooling time of the 800°C metal block simulating the heating of the battery core is 105s and 233s respectively, and the cooling rate of the fire extinguishing agent of Example 1 is about 39% higher than that of the fire extinguishing agent of Comparative Example 7. This shows that the hydrated salt modified material has better cooling performance than the inorganic salt solution, and the high decomposition enthalpy of the hydrated salt plays a significant role.

[0112] (2) Comparing the DSC curves of the battery fire extinguishing agent A-D20 in Example 5 and the battery fire extinguishing agent in Comparative Example 8, the enthalpy values ​​of the two were measured. The results are as follows: Figures 7-8 As shown. The enthalpy value of the inorganic salt solution at the same concentration is only 70% of that of the hydrated salt solution. The hydrated salt itself can undergo a decomposition reaction near the boiling point of water and has a higher decomposition enthalpy, so it has little effect on the heat absorption performance of the material. Compared with hydrated salts, inorganic salts do not have decomposition properties, and high concentrations of inorganic salts significantly reduce the heat absorption performance of water.

[0113] (3) A battery fire extinguishing agent (A-Dx) with a series of concentrations was prepared in Example 5:

[0114] 1) The physical properties of this series of battery fire extinguishing agents were tested, and the test results are as follows: Fig. 9 And the following table 1, where Fig. 9 The left picture in the middle is the DSC curve of the battery fire extinguishing agent, and the right picture is the contact angle test result:

[0115] Table 1

[0116] Material <![CDATA[Density (J / cm 3 )]]> <![CDATA[Volume Enthalpy (J / cm 3 )]]> Mass enthalpy (J / g) A 1.011 2262 2237 A-D20 1.090 2204 2022 A-D40 1.176 2119 1802 A-D60 1.327 2123 1691 A-D80 1.433 2007 1400 DHPD 1.509 1838 1218

[0117] Contact angle measurement method: first heat the material to be tested (A-Dx series battery fire extinguishing agent or DHPD) to 50°C (higher than the melting point of hydrated salt), and then cool the material to be tested to room temperature. Due to the supercooling characteristics of battery fire extinguishing agent, the material to be tested is still liquid at room temperature. Then draw 8μL of the material to be tested and drop it onto the metal surface (316 stainless steel), set up a lighting lamp behind the droplet, and shoot with a camera in front. Finally, use ImageJ software to analyze the contact angle.

[0118] From the above, it can be seen that the A-Dx series battery fire extinguishing agent (hydrated salt solution) has a high decomposition enthalpy, which can effectively cool thermal runaway batteries; it also has a high density, which improves the energy storage density; at the same time, the volume enthalpy value is equivalent to that of pure water materials, and under the same capacity, there is no loss of storage energy; and the contact angle is small, which inhibits the occurrence of film boiling.

[0119] 2) Film boiling inhibition performance test: Test the droplet life of a series of battery fire extinguishing agents on a surface of 100-800°C. The droplet life test steps are: 100 μL of each battery fire extinguishing agent material is added to a preheated metal surface (316 stainless steel, temperature is 100-800°C), and the time from the addition of the material to the end of evaporation is measured. The test results show that the droplet life of the battery fire extinguishing agent (hydrated salt solution) of the present invention is smaller, and the temperature at which the maximum value appears is higher. This shows that the presence of hydrated salts does indeed inhibit the nucleate boiling of water, and a steam film cannot be formed at high temperatures, so the evaporation of water proceeds smoothly. Specifically:

[0120] According to the droplet life-temperature curve (such as Fig.10 ) is used to determine the critical temperature point (Leidenfrost point, LFP) at which film boiling (Leidenfrost effect) occurs in each battery fire extinguishing agent material. The results show that the LFP of the material increases with the increase of the hydrated salt concentration. The LFP of pure water is 300°C, the LFP of 20wt% salt solution is 550°C, and the LFP of 40wt% salt solution is about 750°C. The LFP of salt solution materials with higher concentrations is greater than 800°C. It proves that hydrated salt solutions have a good effect in inhibiting film boiling. High enthalpy chemical energy storage materials can increase the temperature at which water undergoes film boiling, which is beneficial to enhancing the cooling rate of materials on high-temperature walls.

[0121] 3) Battery fire extinguishing test: Use the same flow rate to spray the burning battery that has experienced thermal runaway with battery fire extinguishing agent (heptafluoropropane, perfluorohexanone, water, A-D20 in Example 5). The specific battery used is a 106Ah ternary square lithium battery, and a 1000W heating plate is used to trigger the battery thermal runaway. 5kg of each type of battery fire extinguishing agent is loaded into the material tank (volume is about 6L) in advance, and the nitrogen in the material tank is pressurized to 2.5MPa. Spray the battery fire extinguishing agent immediately after the battery has thermal runaway, and the nozzle is about 60cm away from the battery. The test results of the battery temperature change during and after spraying the battery fire extinguishing agent are as follows. Fig.11 As shown: Fig.11 The left picture is a graph of the temperature change of each battery (the blue shaded area is the time period of battery fire extinguishing agent spraying), the middle picture is a statistical chart of the time that each battery temperature is maintained below 150°C, and the right picture is a statistical chart of the peak temperature rise of each battery after spraying the battery fire extinguishing agent. Fig.12 (The left picture shows the burning state of the thermal runaway battery, and the right picture shows the battery state after spraying A-D20). It can be seen that the low temperature maintenance time of the battery fire extinguishing agent (A-D20) containing high enthalpy chemical energy storage materials in the present invention is higher than that of other materials, which is 22% higher than that of water; the temperature recovery peak value of the A-D20 battery fire extinguishing agent spray is lower than that of other materials, which is 80.2°C lower than that of water. It can be proved that the cooling performance of high enthalpy chemical energy storage materials for thermal runaway batteries is better than that of existing materials.

[0122] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20-30°C. The "between" in the present invention includes the number itself, for example, "between 2-3" includes the endpoint values ​​2 and 3.

[0123] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A battery fire extinguishing agent, characterized in that: The preparation raw materials include water, hydrated salts and auxiliary materials, wherein the auxiliary materials include at least one of nano particles or organic binders, and the mass fraction of the hydrated salts in the preparation raw materials is 10% to 80%.

2. The battery fire extinguishing agent according to claim 1, characterized in that: The hydrated salts include salts that can undergo thermal decomposition; Preferably, the temperature at which the hydrated salt undergoes thermal decomposition is below 150°C; Preferably, the salt capable of thermal decomposition includes at least one of disodium hydrogen phosphate dodecahydrate, sodium dihydrogen phosphate dihydrate, magnesium sulfate heptahydrate, sodium sulfate decahydrate, ammonium phosphate trihydrate, sodium bicarbonate heptahydrate, sodium bicarbonate decahydrate, calcium carbonate hexahydrate, sodium carbonate decahydrate, ammonium ferric sulfate dodecahydrate, aluminum sulfate 18hydrate, sodium aluminum silicate nonahydrate or sodium thiosulfate pentahydrate.

3. The battery fire extinguishing agent according to claim 1, characterized in that: The hydrated salts include at least one of disodium hydrogen phosphate dodecahydrate, magnesium sulfate heptahydrate, sodium sulfate decahydrate, aluminum sulfate 18hydrate, potassium aluminum sulfate dodecahydrate, sodium thiosulfate pentahydrate, copper sulfate heptahydrate, sodium dihydrogen phosphate dihydrate, ammonium phosphate trihydrate, sodium bicarbonate heptahydrate, sodium bicarbonate decahydrate, calcium carbonate hexahydrate, sodium carbonate decahydrate, ammonium ferric sulfate dodecahydrate, aluminum sulfate 18hydrate, sodium aluminum silicate nonahydrate, sodium acetate trihydrate, calcium chloride hexahydrate, sodium silicate pentahydrate, lithium chloride trihydrate, cobalt chloride hexahydrate, aluminum nitrate nonahydrate, calcium sulfate dihydrate or ferrous sulfate heptahydrate; Preferably, the mass fraction of the hydrated salt in the preparation raw material is 15% to 45%.

4. The battery fire extinguishing agent according to claim 1, characterized in that: The nanoparticles include at least one of nano-aluminum oxide, nano-copper oxide, nano-titanium oxide or nano-graphite powder; Preferably, the average particle size of the nanoparticles is 30 to 100 nm; Preferably, the mass fraction of the nanoparticles in the preparation raw material is 0.2% to 5%.

5. The battery fire extinguishing agent according to claim 1, characterized in that: The organic binder includes at least one of polyvinyl alcohol, sodium polyacrylate or carboxymethyl cellulose; Preferably, the mass fraction of the organic binder in the preparation raw material is 0.1% to 2%.

6. The battery fire extinguishing agent according to claim 1, characterized in that: The auxiliary materials also include surfactants; Preferably, the surfactant includes at least one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, Triton 100, Tween 60, Span 60 or polyether-modified silicone oil; Preferably, the mass fraction of the surfactant in the preparation raw material is 0.2% to 5%.

7. The battery fire extinguishing agent according to claim 1, characterized in that: The mass fraction of the water in the preparation raw material is 19% to 84%.

8. A method for preparing a battery fire extinguishing agent, characterized in that: The method comprises the following steps: mixing water, hydrated salts and auxiliary materials to obtain the battery fire extinguishing agent; Preferably, the temperature of the mixing step is comprised between 15 and 70°C.

9. The method for preparing a battery fire extinguishing agent according to claim 8, characterized in that: The hydrated salts include at least one of disodium hydrogen phosphate dodecahydrate, magnesium sulfate heptahydrate, sodium sulfate decahydrate, aluminum sulfate 18hydrate, potassium aluminum sulfate dodecahydrate, sodium thiosulfate pentahydrate, copper sulfate heptahydrate, sodium dihydrogen phosphate dihydrate, ammonium phosphate trihydrate, sodium bicarbonate heptahydrate, sodium bicarbonate decahydrate, calcium carbonate hexahydrate, sodium carbonate decahydrate, ammonium ferric sulfate dodecahydrate, aluminum sulfate 18hydrate, sodium aluminum silicate nonahydrate, sodium acetate trihydrate, calcium chloride hexahydrate, sodium silicate pentahydrate, lithium chloride trihydrate, cobalt chloride hexahydrate, aluminum nitrate nonahydrate, calcium sulfate dihydrate or ferrous sulfate heptahydrate.

10. Use of the battery fire extinguishing agent according to any one of claims 1 to 7 or the battery fire extinguishing agent prepared by the method according to any one of claims 8 to 9 in battery fire extinguishing products; Preferably, the battery comprises at least one of a lithium ion battery or a sodium ion battery.

Citation Information

Cited By

  • New energy photovoltaic and lithium battery general free radical fire extinguishing agent and preparation method

    CN120714193A